Room temperature thin foil SLIM-cut using an epoxy paste: experimental versus theoretical results. (16th April 2015) - Bellanger, Pierre; Bouchard, Pierre-Olivier; Bernacki, Marc; Serra, Joao
Abstract: The stress induced lift-off method (SLIM) -cut technique allows the detachment of thin silicon foils using a stress inducing layer. In this work, results of SLIM-cut foils obtained using an epoxy stress inducing layer at room temperature are presented. Numerical analyses were performed in order to study and ascertain the important experimental parameters. The experimental and simulation results are in good agreement. Indeed, large area (5 × 5 cm 2 ) foils were successfully detached at room temperature using an epoxy thickness of 900 μ m and a curing temperature of 150 °C. Moreover, three foils (5 × 3 cm 2 ) with thickness 135, 121 and 110 μ m were detached from the same monocrystalline substrate. Effective minority carrier lifetimes of 46, 25 and 20 μ s were measured using quasi-steady-state photoconductance technique in these foils after iodine ethanol surface passivation.